Identification of Pathogenic Bacteria on Carp Commodities (Cyprinus carpio) at Quality Control and Fishery Product Safety Agency (BKIPM) of Bengkulu - Wibowo, Risky Hadi (Indonesian Operations Research Association (IORA), 2020)
Carp (Cyprinus carpio) is a type of freshwater fish that is widely cultivated. The increase in the amount of production and trade in freshwater fishery commodities both for consumption in Bengkulu will potentially increase the risk of entry and spread of pests and diseases in fish, which at the same time will be a threat that can endanger and damage the sustainability of fishery biological resources. Bacteria that infect fish can inhibit the expected production targets, which is an outbreak of pathogenic fish disease caused by bacteria. This study aims to identify pathogenic bacteria that infect Carp (C. carpio). Carp were obtained from fish traders at Panorama Market, Bengkulu City. Carp samples were selected based on clinical symptoms that were no longer healthy. Isolation of bacteria from Carp’s organs using Triptic Soy Agar (TSA) media. The isolates were screened by morphological characters and biochemical test. The results of this study showed that total of 2 bacteria were isolated. Based on biochemical tests carried out such as the Simmons Citrate test, Triple Sugar Iron Agar, Oxidative-Fermentative, Motility Indol Ornithine, Lysine Iron Agar, MR-VP, urea, catalase, oxidase, gelatin, confectionery test, and Rimmler-Shotts test, pathogenic isolates Sp 1. in the sample have a close relationship with Plesiomonas shigelloides while the pathogenic isolates Sp 2. and Sp 3. have a close relationship with Aeromonas hydrophila.